COOPERATIVE LEARNING STRATEGY TYPE STAD IN TEACHING ISLAMIC EDUCATION SUBJECT (PAI) AT SMPN 3 LENGAYANG - Zulvia Trinova; Sri Dalena (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
SMPN 3 Lengayang has applied STAD as a type of cooperative learning to improve students’ passiveness. The learning is initiated by forming study groups and assigning tasks to be discussed together. However, in fact the learning is not effective that the students still can not understand the materials properly. It is noticable that the tasks given have been done by one student only, meanwhile the others are less serious and rely on those who are willing to do the group work. This is a field reasearch which describes the implementation of STAD in teaching PAI qualitatively. Data collection techniques used are in the form of observation, interviews, and documentation. As the result; 1) the planning of STAD strategy in teaching PAI at SMPN 3 Lengayang does not yet fulfill the requirement such as in organizing teaching materials (systematic/systematic demands with unsuitable time allocation), and detail of learning scenario (strategy step / method at each stage not clearly illustrated). 2) the implementation of STAD type in teaching PAI at SMPN 3 Lengayang is not fully implemented from the six STAD type cooperative learning steps, namely on teamwork and quiz, and 3) the evaluation in STAD type co-operative learning at SMPN 3 Lengayang is a written test or in the form of quiz. In addition, a test through a special quiz for individual assessment while group assessment is taken from group work. Especially the group with the highest score is given an additional mark.